A Polyphenol-Rich Extract From Entada abyssinica Reduces Oxidative Damage in Cryopreserved Ram Semen - Sobeh, Mansour; Hassan, Soha A.; Hassan, Mahmoud A. E.; Khalil, Wael A.; Abdelfattah, Mohamed A. O.; Wink, Michael; Yasri, Abdelaziz (Frontiers in Veterinary Science, 2020)
The Splinter bean, Entada abyssinica, is widely used in folk medicine. In the current work, we profiled the secondary metabolites from E. abyssinica bark extract using LC-MS and investigated its effect on cryopreserved ram semen. Twenty-eight compounds, including tannins and gallic acid derivatives that prevailed the extract, were tentatively identified. Results showed that the quality of the post-thawed semen showed a significant improvement when the extract was added to the extender at a concentration of 375 µg/mL. The progressive motility and plasma membrane integrity of sperm cells as well as the total antioxidant capacity in the post-thawed semen increased insignificantly. A significant decrease in the concentration of hydrogen peroxide was detected as well. No significant changes were observed in activities of lactate dehydrogenase (LDH), alanine aminotransaminase (ALT) and aspartate transaminase (AST) within the treated samples. Intact sperm percentage was significantly increased while apoptotic and necrotic sperm percentages were reduced significantly. Molecular docking of some individual components from the extract revealed their potential to interfere with the apoptosis cascade in which Bcl-2 is involved. In conclusion, Entada abyssinica appears to be useful for cryopreservation presumably owing to its polyphenol content that has potent antioxidant capacity scavenging reactive oxygen species, enhancing the endogenous antioxidant system and inhibiting lipid peroxidation.